REPRESENTASI NILAI-NILAI KEARIFAN LOKAL DALAM BUKU CERITA ANAK NYADRAN TERBITAN BADAN BAHASA TAHUN 2020: PENDEKATAN SEMIOLOGI SAUSSURE - Alfi Najua Nabila; Adelia Savitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Local culture is an important part of community life because it contains values that are passed down from generation to generation through traditions, language, and customs. This study aims to describe the signifiers and signifieds of cultural symbols as well as the representation of local wisdom values in the children's storybook Nyadran: Belajar Toleransi pada Tradisi by Fajriatun Nurhidayati (2020), published by the Language Development and Fostering Agency. This research employs a descriptive qualitative method using Ferdinand de Saussure’s semiological approach. The data consist of words, sentences, and paragraphs containing cultural elements and local wisdom values in the story text, collected through reading and note-taking techniques. The analysis was conducted by identifying the relationship between signifiers and signifieds in the cultural symbols presented in the story. The findings reveal that the signifiers resik, nyadran, nyekar, kenduri, munjungi, sega golong, ingkung, and pincuk have signifieds related to religiosity, respect for ancestors, togetherness, mutual cooperation, unity, simplicity, and the close relationship between humans and nature. The relationship between these signifiers and signifieds represents the local wisdom values of Javanese society, including religiosity, mutual cooperation, tolerance, togetherness, respect for ancestors, cultural preservation, and simplicity of life. Therefore, the children's storybook Nyadran: Belajar Toleransi pada Tradisi serves not only as reading material for children but also as a medium for cultural education and the preservation of local wisdom for younger generations.